33. SIRS ETHICS COMMITTEE SYMPOSIUM: PREVENTION OF PSYCHOSIS: WHEN AND HOW? THE ETHICAL PERSPECTIVE - Marder, Steve (Schizophrenia bulletin, 2019)
Abstract The Ethics Committee is proposing a special symposium at the SIRS meetings that will focus on ethical challenges in early intervention research. Each of the presentations will address the challenges inherent in trying to prevent an illness when there is uncertainty as to the individual’s true risk. Talks by Drs. Weiser, McGorry, and Perkins will discuss prevention in individuals who fulfill criteria for the at risk or prodromal state. The issue has been discussed in the past and was the subject of a special issue of Schizophrenia Research in 2001. Dr. McGorry will discuss how data from nearly two decades has shaped this area and suggested modifications of prior guidance. Dr. Weiser will discuss the importance of improving our ability to identify individuals who are truly at risk for developing schizophrenia. Dr. Perkins will discuss the relative effectiveness and risk of pharmacological and psychosocial interventions for prodromal symptoms and the ethical issues in selecting interventions. The session will also address challenges in studies of primary prevention. Dr. Freedman will discuss recent studies of a prenatal strategy for preventing schizophrenia and the ethical challenges faced in the design of perinatal interventions. Dr. Carpenter will discuss each of the presentations and will highlight the state of the field.